GAGASAN KHALED ABU FADL TENTANG “ISLAM MODERAT VERSUS ISLAM PURITAN (PERSPEKTIF SOSIOLOGI PENGETAHUAN) - Rusli Rusli (Jurnal Ilmiah Ilmu Ushuluddin, 2009)
The spread of the Islamic puritan movements, which have beeninfluenced by Wahhabism and Salafism, is not positive for Muslimsocieties. According to Abu al-Fadl, the role of moderate Islam tocounter those movements is very important. The main purpose of themoderate Islam project is to establish a strong civil society based ontolerance and respect for human rights. To do this, the moderate Islamtakes the moral values such as equality, justice, and protection of humanlife as the foundation of Islamic law. Therefore, if one finds acontradiction between the literal meaning of religious texts and the basicmoral values, the latter should be prioritized. Moreover, to interpretreligious texts, one does not only need religious traditional knowledge,but also modern social sciences and humanities.